Improved prognosis since 1969 of myocardial infarction treated in a coronary care unit: lack of relation with changes in severity. Issue 6704 (7th October 1989) - Hopper, J. L.; Pathik, B.; Hunt, D.; Chan, W. W.
Abstract : OBJECTIVE--To study changes from 1969 to 1983 in the prognosis of patients with acute myocardial infarction treated in a coronary care unit. DESIGN--Mortality follow up of all patients with definite acute myocardial infarction. SETTING--The coronary care unit of the Royal Melbourne Hospital, a tertiary referral centre. SUBJECTS--4253 Patients (3366 men, 887 women) admitted from 1969 to 1983. MAIN OUTCOME MEASURE--Mortality recorded at discharge from hospital and 12 months after admission. RESULTS--Details of clinical findings, history, electrocardiograms, arrhythmias, and radiological findings were recorded on admission. Mean ages were 63 for women and 57 for men, and women had haemodynamically more severe infarcts than men. In the later years patients were older and had less severe infarcts. Overall, hospital mortality in men was 16.7% in 1969-73 and 8.5% in 1979-83 and declined in all grades of the Norris and Killip infarct severity indices compared with a constant 19.2% in women. Even after adjustment for age and severity by logistic regression, hospital mortality fell in men by an average of 8% (95% confidence interval 4% to 11%) a year but remained constant in women. By 1983 male mortality was 60% that of women of similar age and comparable severity of infarction. Mortality of hospital survivors at 12 months declined by 7% (4% to 9%) a year in both sexes, even after adjustment for age and severity, with a male to female mortality ratio of about 0.8. New indices were derived to predict mortality in hospital and at 12 months. CONCLUSION--The observed declines in mortality cannot be explained by changes in severity of infarction or in prognostic characteristics of patients.